A more realistic approach towards concrete delivery dispatching problem: using real distance instead spatial distance. Issue 1 (2nd January 2018) - Muniz de Miranda Sá, Júlia; Maghrebi, Mojtaba
Abstract: The Ready Mixed Concrete Dispatching Problem (RMCDP) is a generalised version of the Vehicle Routing Problem (VRP). In RMCDP however, given the particular properties of concrete, a set of additional constraints must be considered. The perishability of fresh material, for example, has to be contemplated, together with other technical issues, such as a truck can only serve a single customer and two or more customers cannot be supplied using a truck in a single trip. RMCDP can be modelled as a mixed integer problem (with soft time window) and it can be optimally solved for small and medium sized variants of the problem. However, the objective cost and similar constraints are usually calculated using spatial distances (Euclidian distance) and similar approximate travel times are used. In this paper, we propose a more realistic method for calculating travel times based on real travel distances obtained from Google Maps API. The accurate travel time information is used as input for the RMCDP, to provide results that are more convincing. This paper compares  RMCDP with two different objective functions; (i) spatial distance and (ii) real distance. This research will clarify the influence that the quality of this information has on the decision-making process and whether it is relevant to regard the accurate travel time to achieve a more realistic result.